Model Pembelajaran Problem Based Learning (PBL) Berbasis Pendekatan Saintifik Untuk Penguatan Keterampilan Berpikir Kreatif Siswa Kelas V Sekolah Dasar Negeri 1 Pakisari Klaten - Armani, Muhammad Risqi Cahya; Rosanawati, I Made Ratih (Jurnal Gentala Pendidikan Dasar, 2025)
This study aims to describe the Problem Based Learning (PBL) learning model based on a scientific approach in strengthening the creative thinking skills of fifth grade students at SD Negeri 1 Pakisari, Klaten. The background of this study is based on the low creative thinking skills of students due to the dominance of conventional methods centered on teachers. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the application of the scientific-based PBL model has a positive impact on increasing student active participation, the ability to identify and solve problems, and the ability to communicate ideas systematically. The scientific approach through the stages of observing, asking, trying, reasoning, and communicating encourages students to think logically, analytically, and creatively. Although faced with challenges such as time management and varying student readiness, this model is considered capable of building learning independence and improving the quality of learning as a whole.